PROSES PENERAPAN TEKNIK QUILTING PADA PEMBUATAN JAKET DENIM - Romdhona Chusna Tsani; Putri Shaila (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
The denim jacket is one of the fashion needs young people have to have for stylish needs. Not only was the durability of the denim jacket also made clothing that was easily combined with various garments. While the denim jacket also has certain wear, the denim model tends to have simple cuts, besides the type of denim itself being monotonous and without motive. Thus the application of quilting technique was fitting to show a newer jacket with a striking combination of cloth on quilting's motive. The purpose of the denim jacket was to know the process of applying quilting techniques on the denim. The methodology used was observation methods, literature methods and documentation methods. The process of application of quilting techniques on the making of denim jackets goes through three stages of designing denim jackets, the preparation of tools and materials, specifying sizes, creating basic patterns, breaking jacket patterns, cutting materials, merader materials, and sewing. Quilting's pattern requires high concentration and precision because it has to watch the angles of the motif connection. A concern when quilting was an polyester layer of layered foam that tended to be slippery shifted the furs. Therefore furing cuts need to be wider than the patchwork pattern. The thickness of the layer of foam should not be too thick because it will make the jacket rigid and heavier.